The C-3 acylation of 1-hydroxyindoles. Issue 8 (22nd February 2017) - Chirkova, Zhanna V.; Kabanova, Mariya V.; Filimonov, Sergey I.; Abramov, Igor G.; Samet, Alexander V.; Stashina, Galina A.; Suponitsky, Kyrill Yu.
Graphical abstract: Highlights: The first direct C-3 acylation of 1-hydroxyindole derivatives was accomplished. Aliphatic anhydrides were used as acylating agents and BF3 ·Et2 O as a promoter. Intermediate 3-acyl-1-acyloxyindoles were readily hydrolyzed to 3-acyl-1-hydroxyindoles. Abstract: The C-3 acylation of 1-hydroxyindole derivatives with aliphatic acid anhydrides was accomplished in high yields using BF3 ·Et2 O as a promoter, affording the corresponding 3-acyl-1-acyloxyindoles which in turn were readily hydrolyzed to the corresponding 3-acyl-1-hydroxyindole derivatives.